Effects of tropical forest fragmentation on ecology and conservation of migrant and resident birds in lowland Costa Rica - Roberts, Dina L. (2007)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho